Decision strategies for policy decisions under uncertainties: The case of mitigation measures addressing methane emissions from ruminants. Issue 52 (October 2015) - Hirsch Hadorn, Gertrude; Brun, Georg; Soliva, Carla Riccarda; Stenke, Andrea; Peter, Thomas
Highlights: Decisions should account for uncertainties in options, outcomes and values. Decision strategies enable deliberation and learning about uncertainties. Decision strategies support appropriate problem framing and decision timing. Uncertainty of nutritive options to mitigate CH4 from ruminants speaks against closure. Abstract: Decision strategies aim at enabling reasonable decisions in cases of uncertain policy decision problems which do not meet the conditions for applying standard decision theory. This paper focuses on decision strategies that account for uncertainties by deciding whether a proposed list of policy options should be accepted or revised (scope strategies) and whether to decide now or later (timing strategies). They can be used in participatory approaches to structure the decision process. As a basis, we propose to classify the broad range of uncertainties affecting policy decision problems along two dimensions, source of uncertainty (incomplete information, inherent indeterminacy and unreliable information) and location of uncertainty (information about policy options, outcomes and values). Decision strategies encompass multiple and vague criteria to be deliberated in application. As an example, we discuss which decision strategies may account for the uncertainties related to nutritive technologies that aim at reducing methane (CH4 ) emissions from ruminants as a means of mitigating climate change, limiting our discussion to published scientific information. These considerations not only speak in favour of revising rather than accepting the discussed list of options, but also in favour of active postponement or semi-closure of decision-making rather than closure or passive postponement.